PENERAPAN SISTEM HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) PADA INDUSTRI RUMAH TANGGA TAPE DI WILAYAH KECAMATAN SUKOSARI, KABUPATEN BONDOWOSO - Ikhris Syafira rengganis; Narwati; Ernita Sari; Rusmiati; Pratiwi Hermiyanti (Poltekkes Kemenkes Surabaya, 2023)
In the application of the hazard analysis and critical control point in the tape householdindustry in the Sukosari area, there are still several components that do not meet therequirements, such as the area where the processing is not clean, the use of rusty foodprocessing equipment, food equipment and food ingredients that are not rinsed with cleanwater, the food packaging room that is not tightly packed with vectors, and not wearinggloves when handling food . The purpose of this study is to describe the application ofhazard analysis and critical control points in the household tape industry in the District ofSukosari, Bondowoso Regency.This type of research is descriptive and observational with the object of research beingthe entire home industry of tape production in the District of Sukosari with a population of2 IRTP. The research variables studied included the application of hazard identification,determination of CCP, determination of critical limits, monitoring of CCP, corrective actions,application of hazard analysis and critical control point systems and descriptive dataanalysis.The results showed that the application of hazard identification was in good category(70%), the determination of CCP was in a sufficient category (65%), determination ofcritical limit was in good category (80%), monitoring of CCP was in sufficient category(50%), corrective action was in good category (75%) so that the application of the hazardanalysis and critical control gets a good category (68.41%).The advice given to handlers is to wash their hands regularly after and before theproduction process and not use their hands directly when touching food. The IRTP paysmore attention to hygiene and sanitation in the processing of food production and routinelyperforms cleaning and maintenance at the production site.